First records of Croatian and Serbian Tetrigidae (Orthoptera: Caelifera) with description of a new subspecies of Tetrix transsylvanica (Bazyluk & Kis, 1960) - Skejo, Josip; Rebrina, Fran; Buzzetti, Filippo Maria; Ivković, Slobodan; Rašić, Alan; Tvrtković, Nikola (Zootaxa, 2014)
A review of the Croatian and Serbian Tetrigidae is given and first records of Tetrix undulata (Sowerby, 1806) for Croatia and Serbia as well as Tetrix tuerki (Krauss, 1876) and Tetrix transsylvanica (Bazyluk & Kis, 1960) comb. nov. for Croatia are presented. The status of the genus Uvarovitettix Bazyluk & Kis, 1960 and the taxonomic position of T. transsylvanica comb. nov. are discussed. The genus Uvarovitettix Bazyluk & Kis, 1960 syn. nov. is synonymised with the genus Tetrix Latreille, 1802. A new subspecies from Croatia and Slovenia, Tetrix transsylvanica hypsocorypha Skejo, 2014 subspecies nova, is described. Tetrix pseudodepressa (Ingrisch, 2006) comb. nov. and Tetrix depressa (Brisout de Barneville, 1848) comb. nov. are moved to the genus Tetrix and the genus Depressotetrix Karaman, 1960 syn. nov. is synonymised with the genus Tetrix. Tetrix gibberosa (Wang & Zheng, 1993) inc. sed. and T. nodulosa (Fieber, 1853) inc. sed. are now considered to be species of uncertain placement within the genus Tetrix. New combination is also given to Paratettix tuberculata (Zheng & Jiang, 1997), primarily placed within the genus Mishtshenkotetrix: Tetrix tuberculata (Zheng & Jiang, 1997) comb. nov., but its placement within the genus Tetrix is also uncertain.